REASONS OF USING CODE SWITCHING BY THE HEAD OF UNIVERSITAS MAHAPUTERA MUHAMMAD YAMIN IN THE SPEECHES ON GRADUATION DAY - Leli Lismay (JEE (Journal of English Education), 2017)
The research is based on phenomenona occurs in a multilingual community that tend to use more than one language in communication. The phenomenon is called code transfer which does not only happens in informal situation but also in formal situation, like in speech of university leader, especially the head of Mahaputera Muhammad Yamin University Solok, West Sumatera. The purpose of this study was to analyze the reasons of using code switching by the leader of university in their speech during the graduation ceremony. This research used descriptive qualitative methods, where speech script was a source to be studied and analyzed. Based on the analysis, it was found that the tendency of using code switching was due to the educational background that was taken by the university leader, and also several other reasons related to language habits in multilingual community itself.